An Analysis of the Stress State in Powder Compacts during Unloading, Emphasizing the Influence from Different Frictional Models - Hjalmar Staf; Per-Lennart Larsson (Applied Sciences, 2023)
Finite element (FE) simulations are frequently used nowadays in order to analyse powder compaction and sintering, for example, when determining the shape of a cutting blank insert. Such analyses also make it possible to determine in detail the stress state in a powder compact during loading and unloading. This is certainly important as (residual) tensile stresses can lead to cracking, either after unloading or during the subsequent sintering step. The magnitude of plastic deformation is also an issue here. Concerning the stress state in the powder compact, the frictional behaviour (between walls and powder compact) is of great importance. For this reason, in the present study, two frictional models are implemented into a commercial FE software, and numerical results based on the stress state before and during unloading are derived. The two friction models produce quite different results, and it is obvious that the frictional behaviour at powder pressing has to be carefully accounted for in order to achieve results of high accuracy.